1975
DOI: 10.1093/ajcn/28.11.1223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal nutrition on birth weight

Abstract: This paper discusses some conditions necessary to detect an effect of maternal nutrition on birth weight and the relative contribution of calories and protein to such an effect. The expected dose- and time-response relationships for nutritional interventions aimed at the improvement of birth weight are also discussed. There appears to be a minimal level of nutrients which must be available in order to obtain adequate birth weight. However, above this minimum level, pregnant women can adapt themselves to a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
5

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(56 citation statements)
references
References 29 publications
4
46
1
5
Order By: Relevance
“…Previous studies have established that malnourished pregnant women are at increased risk of having LBW infants [5,6]. The link between LBW and poor health and nutritional outcomes later in life is also well established, with several studies reporting the association of LBW with malnutrition, poor growth and development, and increased morbidity and mortality in children [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have established that malnourished pregnant women are at increased risk of having LBW infants [5,6]. The link between LBW and poor health and nutritional outcomes later in life is also well established, with several studies reporting the association of LBW with malnutrition, poor growth and development, and increased morbidity and mortality in children [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Food supplementation programs influence prenatal nutrition (38) and social conditions (54) and could thereby influence maternal-infant interaction through both biological and social pathways. A potential biological pathway exists in which mothers who consume more nutrients beginning earlier in gestation experience better health and their infants have better fetal growth and development than mothers who consume fewer nutrients or consume them later in gestation (9,33,38,55). As shown in animal studies, better maternal nutrition leads to better placental function and fetal development, even if fetal growth or size is not influenced (56).…”
Section: Discussionmentioning
confidence: 99%
“…While the effects of maternal under-nutrition on fetal growth have been extensively studied (Lechtig et al 1975;Godfrey, 1998), little is known about the effects of materno-fetal oxygen deprivation. Previously, it was reported that high altitude, rather than maternal economic status, is associated with reduced mean birth weight and increased infant mortality in Bolivia (Giussani & Barker, 1999).…”
Section: Department Of Physiology University Of Cambridge Downing Smentioning
confidence: 99%